Pengaruh laju aliran biogas dan waktu penyalaan Terhadap kinerja motor bakar menggunakan sistem dual fuel pertamax-biogas - Mafruddin, Mafruddin; Irawan, Dwi; Pratama, Edwin Dian; Pratama, Renno yoga (Universitas Muhammadiyah Metro, 2021)
Fuels such as oil, coal and gas are non-renewable energy sources. For this reason, renewable energy sources are needed to replace these non-renewable energy sources. The use of biogas as a renewable energy source for gasoline motor fuel can be done using a dual fuel system (pertamax-biogas). Combustion on a gasoline engine with a dual fuel system will affect the resulting performance. The combustion process in the combustion engine is influenced by several factors including the biogas flow rate and ignition time. The purpose of this study was to determine the effect of biogas flow rate and ignition timing on the performance of a motorcycle engine with a dual fuel system. The method used in this study is an experimental study by testing the performance of a motorcycle engine using a dual fuel system with variations in the flow rate of biogas fuel 1 lpm, 2 lpm and 3 lpm and variations in ignition time of 11°, 13° and 15°. before TDC. From the results of the study it can be concluded that the biogas flow rate and ignition timing affect the performance of the motor. The highest power was obtained by varying the biogas flow rate of 2 lpm and ignition time of 15° before TDC, while the best specific fuel consumption was obtained at variation of the biogas flow rate of 3 lpm and ignition time of 15° before TDC.